Athabasca, AB - Panoramic View in 1912 - 01 - (Author); (Interviewer); (Publisher) (1912)
Photograph - A view of the town of Athabasca, Alberta from north of the Athabasca River. This photo joins with 00934 and 00939 to make a panoramic view